Predominance of antimicrobial resistance genes and high-risk clones among Gram negatives from clinical sources in Accra-Ghana - William Boateng; Christian Owusu-Nyantakyi; Felicia Owusu; Grebstad R. Amuasi; Quaneeta Mohktar; Pernille Nilsson; Bright Adu; Rene S. Hendriksen; Beverly Egyir (PLoS ONE, 2026)
Gram-negative bacteria species cause increasing levels of antimicrobial resistance worldwide. Enhanced surveillance efforts are required to inform treatment decisions and monitoring of the rise and spread of antimicrobial resistant (AMR) clones, especially on the African continent, where antimicrobial resistance is known to be least tackled and controlled. In this study, whole genome sequencing was used to investigate a collection of Gram negatives recovered from clinical sources. Bacterial species were identified by Matrix-assisted Laser Desorption/Ionization Time of Flight mass spectrometry. Whole genome sequencing was performed using the Miseq illumina platform, and sequence data were analysed using free online bioinformatics tools.  Of the 182 isolates investigated, 62 resistant to at least one antibiotic were selected for whole genome sequencing. Among these, Escherichia coli (n=21; 33.87%) and Klebsiella pneumoniae (n=13; 20.97%) were the predominant Enterobacterales, while Pseudomonas aeruginosa (9/16; 56.25%) was most common among non-Enterobacterales. The 62 Isolates sequenced were from wound (n=37),  urine (n=19), blood (n=5), and pus (n=1). In total, 49 isolates were found to exhibit multidrug resistance (MDR). Genomic analysis revealed 126 resistance gene types, with beta-lactamase-encoding genes being the most common (56/126; 44.44%), detected in 90.32% (56/62) of organisms. K. pneumoniae (13/13; 100%) and Klebsiella oxytoca (1/1; 100%) exhibited coexisting OqxA and OqxB efflux pump genes. All E. coli isolates carried the MDR gene mdf(A) . An Enterobacter kobei wound isolate carried the colistin resistance gene mcr-10 . The quaternary ammonium compound resistance gene qacE was present in 50% (31/62) of isolates. Additionally, 41.94% (26/62) of isolates harbored the traT virulence gene.. High-risk clones detected included MDR ST131 E. coli serotype O25:H4 (6/21; 28.57%), ST15 and ST147 K. pneumoniae , and ST244 P. aeruginosa . Salmonella enterica serovars Lille and Typhi recovered from blood were also identifed. The study revealed high risk clones of Gram negatives carrying multiple AMR and virulence genes. The detection of MDR pathogens and global high-risk clones, highlights the need for effective surveillance and the use of whole genome sequencing to strengthen antimicrobial resistance monitoring in our setting.